CO2 enrichment from flue gas for the cultivation of algae – a field test. Issue 5 (26th May 2015) - Wolff, Thorsten; Brinkmann, Torsten; Kerner, Martin; Hindersin, Stefan
Abstract: A membrane unit in pilot scale is operated to provide a CO2 ‐enriched product stream from flue gas of a natural‐gas‐fuelled heating system. The CO2 stream is fed to a cultivation medium of photobioreactors that are integrated in the façade of the building project 'BIQ – The Algae House' (International Building Exhibition 2013/Hamburg), where CO2 is required as the carbon source for the growth of algae, which are cultivated in the bioreactors. This work presents a long‐term field test. Furthermore, a possibility for the usage of CO2 separated de‐centrally is given. The operational conditions for the membrane module cause additional mechanical stress on the membrane material since the pilot plant is operated with periodic start‐ups and shut‐downs. The occurrence of acidic water on the membrane generates additional potential damage of the material. The field test is planned to be carried out for several years to prove the reliability of this membrane technology in flue gas treatment. © 2015 Society of Chemical Industry and John Wiley & Sons, Ltd